Peningkatan Keterampilan Motorik Kasar Anak Usia 4-5 Tahun Melalui Permainan Tradisional Tambi-Tambian - Iis Verawati Simatupang (PG-PAUD Trunojoyo, 2018)
The aim of this research is to enhance the children’s gross motor skill through traditional games “Tambi-tambian”. Traditional games are very useful for the basic development of children and through it children recognize and preserving local culture. The research was conducted among 11 children of group A at TK Nasional KPS Balikpapan. The procedures for this action research using Kemmis and McTaggart’s model through four stages: planning, action and observation, reflection. The data were collected using interview, observation, and documentation. Data analysis is carried using both quantitative and qualitative analysis. The results of research show enhancement of gross motor skill through traditional games “Tambi-tambian”. Pre-intervensi, children’s gross motor skill is 53,41%, after the conducted action children’s gross motor skill increasing in the 1st cycle is 68,86% and 2ndcycle is 81,59%. Traditional games “Tambi-tambian” contributes to enhance children’s gross motor skill.